EXPLORING THE INFLUENCE OF SUBJECTIVE NORMS, PERCEIVED BEHAVIORAL CONTROL, AND ATTITUDES ON TRUST IN ISLAMIC BANKS: AN EMPIRICAL ANALYSIS - Muhammad Adeel; Muhammad Umer Quddoos; Arslan Ahmad Siddiqi; Mazhar Iqbal, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
PurposeIn today’s business world, customer trust is key to managing a business. This study aims to examine the impact of three constructs of the theory of planned behavior including Subjective Norms, Perceived Behavior Control, and Attitude on trust in Islamic Banks (IBs).Design/Methodology/ApproachWe collected data through an online questionnaire. Judgmental/purposive sampling was used. We employed 164 responses in the analysis. Partial Least Square Equation Modeling (PLS-SEM) was employed to analyze the data for which Smart PLS software version 4 was used.FindingsThe results show that Subjective Norms, Perceived Behavior Control, and Attitude positively and significantly impact Trust in Islamic Banks.Research Limitation/ImplicationWe focused on Subjective Norms, Perceived Behavior Control, and Attitude only. Moreover, this study was conducted in a single country. Therefore, for future research, we suggest conducting a cross-country analysis employing other antecedents of trust.Practical ImplicationsBased on research findings, Islamic Bank managers have input on how to improve Trust in IBs. They can revamp marketing strategies accordingly.Originality/ValueThis study is an attempt to study Subjective Norms, Perceived Behavior Control, and Attitude as antecedents of Trust in IBs.